Pengaruh Kepuasan Kerja dan Disiplin Kerja Terhadap Kinerja Pegawai Kantor Camat Kecamatan Kapuas Kabupaten Sanggau - Yanti, Yanti; Firayanti, Yuni; Saputra, Edy Suchmawan (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study was conducted to analyze the influence of job satisfaction and work discipline on employee performance at the District Office of Kapuas Subdistrict, Sanggau Regency. The background of this research arises from the phenomenon that some employees still lack discipline in carrying out their duties, which affects the level of job satisfaction and in turn reduces the quality of public services. The research method employed was a quantitative approach using multiple linear regression analysis. The sample consisted of 30 employees determined through saturated sampling technique. The research instrument was a closed questionnaire constructed based on indicators of job satisfaction, work discipline, and employee performance. Data were analyzed with the assistance of SPSS version 23 through validity testing, reliability testing, regression analysis, t-test, F-test, and the coefficient of determination (R²). The results showed that job satisfaction had a positive and significant effect on employee performance, with a t-count value of 4.529 > t-table 1.703 and a significance level of 0.000 < 0.05. Work discipline also had a positive but not significant effect on performance, with a t-count of 1.721 > t-table 1.703 and a significance level of 0.097 > 0.05. Simultaneously, job satisfaction and work discipline had a significant effect on employee performance, with an F-count value of 20.606 > F-table 2.51 and a significance level of 0.000. The coefficient of determination (R²) of 0.604 indicated that 60.4% of the variation in employee performance was explained by the two independent variables, while the remaining 39.6% was influenced by other factors outside this study. It can be concluded that improving employee performance in subdistrict offices can be achieved through enhancing job satisfaction, for instance by providing adequate work facilities such as desks and chairs, creating a comfortable work environment, granting recognition, as well as enforcing consistent work discipline. This study is expected to serve as a reference for local governments in formulating more effective human resource management policies.